Penerapan Model Quantum Writing dalam Meningkatkan Keterampilan Menulis Argumentasi Siswa - Purlilaiceu, Purlilaiceu; Maryana, Dede (Jurnal Artikula, 2019)
This research is motivated to create a pleasant learning atmosphere or situation and create a productive learning process and change the teaching paradigm into learning, with this change the educational process into a process of how to learn together between teachers and learners and apply the right learning methods. Based on the results of the initial survey conducted by researchers showed that the quality of writing learning in Indonesian subjects in class XI students has not reached the minimum completion criteria (KKM) limit, this can be seen from the results of writing test scores that have not reached the target and the average grades of students obtained during the paragraph or essay writing test. In accordance with the development of science and technology have also emerged several new learning methods that are breakthroughs such as quantum writing methods in writing essays. This research uses action research methods focused on classroom situations, commonly known as classroom action research. Data collection techniques that are carried out include observations / observations, namely activities carried out by researchers and collaborators to observe students in Indonesian learning. As for the results of recapitulation of data or grades of students of grade XI IPA 3 in writing exposition essays using quantum writing models in cycle I obtained an average of 74 and cycle II obtains an average score of 79, with the minimum completion criteria specified by the basic competence of writing exposition which is 78. So the target of achievement of the goal in the writing skills of the exposition essay is 90% achieved or successful means that students are able to write well.